Natural killer cell granule protein 7 contributes to CD8+ T cell-mediated platelet apoptosis in immune thrombocytopenia - Xiaolin Wang; Qiang Liu; Xiaojing Li; Wei Xing; Ping Chen; Qi Feng; Ming Hou; Qian Wang; Hai Zhou; Jun Peng (Research and Practice in Thrombosis and Haemostasis)
Background: CD8+ T cells participate in the pathogenesis of primary immune thrombocytopenia (ITP). Natural killer cell granule protein 7 (NKG7) is essential for natural killer cell and CD8+ T cell cytotoxicity. The function of NKG7 in CD8+ T cells in ITP remains unclear. Objectives: We investigated the expression and roles of NKG7 in CD8+ T cells in ITP. Methods: We analyzed NKG7 and CD107a expression and CD8+ T cell-mediated platelet apoptosis in patients with ITP and controls. NKG7 knockdown was performed using small interfering RNA, and the extracellular signal-regulated kinases 1 and 2 pathway was analyzed by western blot analysis. Results: NKG7 was significantly increased in CD8+ T cells and positively correlated with CD107a and CD8+ T cell-induced platelet apoptosis in ITP. Based on NKG7 levels, patients with ITP were divided into NKG7 high-expression and low-expression groups. Patients with high expression of NKG7 had significantly higher levels of CD107a and CD8+ T cell-induced platelet apoptosis than controls, whereas no difference was found between patients with low NKG7 expression and controls. Platelet counts in patients with high NKG7 expression were significantly lower than those in patients with low NKG7 expression. We knocked down NKG7 in CD8+ T cells from patients with ITP and found decreased CD107a expression and less platelet apoptosis in vitro. We further found that NKG7 affected the cytotoxicity of CD8+ T cells through the extracellular signal-regulated kinase 1 and 2 pathway. Conclusion: NKG7 plays an important role in CD8+ T cell-mediated cytotoxicity might be a potential therapeutic target for ITP.